Transition from isolated to interacting copper( ii ) pairs in extended lattices evaluated by single crystal EPR spectroscopy - Neuman, Nicolás Ignacio (2015)
We report the synthesis and X-ray structure of the dimeric zinc(II) compound [Zn(tda)(phen)]2∙H2tda,(tda = thiodiacetic acid, phen = 1,10-phenanthroline) hereafter Zn(tda)(phen),and a single crystal EPR study of Zn(tda)(phen) doped with Cu(II) ions. Zn(tda)(phen)is isomorphous to its Cu(II) analogue. The EPR spectra show a central signal composed of one to four resonances assigned to Cu-Zn heterodimers, flanked by less intense satellite signals assigned to Cu-Cu homodimers. Analysis of single crystal EPR data allowed us to determine the g- and A-matrices of theCu(II) ion and the anisotropic ZFS parameters of the homodimer. Within the experimental error, the Cu(II) g-matrix obtained for the diluted compound was identical to that previously determinedby us in pure Cu(tda)(phen). The ZFS is shown to be dominated by magnetic dipolar coupling between the unpaired electrons mainly centered around theCu(II) ions, although partially delocalized over the equatorial copper ligands. DFT calculations yielded spin population values compatible with those determined from the analysis of the anisotropic ZFS assuming a distributed dipole model. The information obtained from the diluted compound was used to evaluate the interdimeric exchange interaction between dimeric units in pure Cu(tda)(phen). The comparison between both point and distributed dipole approximations is discussed with reference to the analysis of the EPR data.